RAMBU SOLO’ AS A SOURCE OF ETHNOPEDAGOGY: INTEGRATING ETHNOMATHEMATICS AND INDONESIAN LANGUAGE LITERACY THROUGH TORAJAN LOCAL WISDOM - Rubianus Rubianus (Jurnal Vokatif: Pendidikan Bahasa, Kebahasaan, dan Sastra, 2026)
Rambu Solo’ is one of the most significant cultural traditions of the Torajan community. Beyond its ritual function, the tradition contains local knowledge that can be transformed into meaningful learning resources. This study aims to explore the potential of Rambu Solo’ as a source of ethnopedagogy that integrates ethnomathematics and Indonesian language literacy. The study employed a qualitative approach with a descriptive ethnographic design. Data were collected through observation of Rambu Solo’ practices, interviews with traditional leaders, religious leaders, bereaved families, and community members, as well as documentation and literature review. Data were analyzed through data reduction, categorization, data presentation, interpretation, and conclusion drawing. The findings indicate that Rambu Solo’ contains various forms of mathematical knowledge, including numbers, counting, measurement, comparison, proportion, geometry, spatial organization, and patterns. At the same time, the tradition provides rich linguistic resources, including cultural terms, oral expressions, narratives, interpersonal communication, and descriptions of ritual activities that can be developed into learning materials for listening, speaking, reading, and writing. These findings suggest that Rambu Solo’ can serve as an interdisciplinary learning context connecting mathematics, language, culture, and students’ everyday experiences. Integrating ethnomathematics and Indonesian language literacy through local cultural practices can support contextual learning while strengthening students’ cultural awareness and appreciation of local heritage.